HUBUNGAN ANTARA SENSITIFITAS ANTARBUDAYA, PENGETAHUAN ANTARBUDAYA, DAN EFEKTIVITAS ANTARBUDAYA PADA KOMUNITAS MULTIETNIS - Ahadi, Muhammad Nur (Master of Communication Science Program, Faculty of Social and Political Science, Diponego, 2016)
AbstractThe purpose of this research was to explore the relationship among the variables: intercultural sensitivity, intercultural awareness, and intercultural effectiveness. The survey research method was used to collect data from 51 residents of multiethnic community at Kampung Pemali, Semarang. Overall, residents of Pemali Neighborhood reported high level of intercultural sensitivity, intercultural awareness, and intercultural effectiveness. The result of Kendall’s tau-b correlations confirm the positive relationship between intercultural sensitivity and intercultural effectiveness (R=0,351 p=0,009), the positive relationship between intercultural awareness and intercultural effectiveness (R=0,297 p=0,026), and the positive relationship between intercultural sensitivity and intercultural awareness (R=0,351 p=0,008).Keywords: intercultural sensitivity; intercultural awareness; intercultural effectiveness; intercultural communication competence